Understanding Mechanisms of Resilience Economy- Live Application on a Complex Business Model - Buheji, Mohamed (Advances in Social Sciences Research Journal, 2017)
"Resilience" as a concept has been re-discovered by many researchers from different disciplines in the last few years as it answers the demands for sustainable dynamical systems and way thinking that need to be addressed to rehabilitate different problems in our world today. This paper reviews the concept of resilience in order to develop from it a proposed mechanism for tackling problems and techniques that would lead to inspiration of the business model of any organization or society. An application of the proposed mechanism is implemented on the Water Supply Service loss and leakages as a challenging problem that is faced usually by most of the water utility and authority companies all over the world, but with varying magnitude, is reviewed. Being a complex business model, going through different challenges in many developed and developing countries, resilience mechanism is applied to identify how to improve the capacity of the system and make it more resilient without increasing its expenditure or affecting it supply stability. The study goes to see how the mechanism of resilience economy, adopted from the literature reviewed, could help to contribute to our understanding of the evolution of such system mechanism if we really to adopt a resilient mindset.